PERBAIKAN KOMPUTER DAN PRINTER UNTUK MENINGKATKAN MUTU PELAYANAN SEKOLAH PADA MIS AL-ISLAMIYAH BATU PUTIH DESA ALILA TIMUR KECAMATAN KABOLA, KABUPATEN ALOR-NTT - Karolina Karsa; Nimrot Ambrosius Potmo; Merari Botau; Junaldi Laure; Melisa Asnat Padahana; Ishak Maniyeni; Jon Idrison Molina; Julminggu J. Selly (Intimas, 2026)
The development of information technology requires educational institutions to have adequate facilities to support administrative services and learning activities. However, limited technological infrastructure remains a challenge for schools in rural areas, including MIS Al-Islamiyah Batu Putih, Alila Timur Village, Kabola District, Alor Regency. This community service activity aims to improve school service quality through the repair of damaged computers and printers. The implementation method consisted of observation, damage diagnosis, hardware and software repair, functionality testing, and evaluation. The results show that one printer and two computers that were previously unusable have been restored to normal operation after repair and system reset, while one computer requires further action in the form of display cable replacement. The repaired devices improved the efficiency of teachers and administrative staff and supported smoother school administrative services. Therefore, this community service activity contributes positively to strengthening the utilization of information technology as a strategic effort to enhance the quality of educational services in schools.